Entrepreneurial Mindset, Orientation, and Performance of University Students in Indonesia - Eddy Madiono Sutanto; Evan Lau; Andreas Ezra (Universitas Hayam Wuruk Perbanas, 2021)
Entrepreneurship plays an important role in determining the level of economic growth of a country. This study aims are to explorethe impact of entrepreneurial mindset on innovativeness, risk-taking, competitive aggressiveness, autonomy, and proactiveness onentrepreneurial performance. This research uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze thedata.. It gathered data of 364 respondents, which were the bachelor students of management program of public universities inSurabaya, Indonesia. The results show that entrepreneurial mindset has a significant impact to innovativeness, risk-taking,competitive aggressiveness, autonomy, and proactiveness. It also enhances positive and significant impact to entrepreneurialperformance of the students. It implies that the entrepreneurship education of public universities in Surabaya, Indonesia succeedsto change the students’ mindset and orientation. The government needs to increase entrepreneurship education centers andbusiness incubator centers at various universities.